ИСТОРИЧЕСКАЯ РЕАЛЬНОСТЬ И ХУДОЖЕСТВЕННОЕ МАСТЕРСТВО ПОЭТА - Мамбетов, К. (SCIENCE and SOCIETY, 2021)
The article examines the literary genre, type, genre and genre form of the poem in the Karakalpak literature. And also given the author's conclusion of the scientific analysis of the poem, as a literary form in the poetry of I.Yusupov.
Keywords: history; poem; genre; type; plot; epic; lyro-epic